Tinjauan Naratif: Efektivitas dan Mekanisme Cranberry (Vaccinium macrocarpon) dalam Pencegahan Infeksi Saluran Kemih - Alwin Ardiansyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Urinary Tract Infection (UTI) is a common bacterial infection that frequently recurs in women, predominantly caused by Escherichia coli. The increasing antibiotic resistance has prompted the search for non-antibiotic preventive strategies, including the use of cranberry (Vaccinium macrocarpon). This narrative review aims to synthesize recent scientific evidence regarding the mechanisms of action and clinical efficacy of cranberry. The main biological mechanism involves inhibition of bacterial adhesion by Type-A proanthocyanidins (PACs), preventing E. coli from attaching to the bladder wall. Although in vitro studies consistently demonstrate this effect, clinical trials show heterogeneous outcomes. Some randomized controlled trials (RCTs) report significant reductions in recurrent UTIs among women and postoperative patients, while others find no statistical difference compared to placebo. These inconsistencies are largely due to variations in study design, PAC dosage, and patient compliance. Evidence consistently indicates that cranberry is ineffective for acute UTI treatment but may serve as a valid prophylactic strategy in selected high-risk populations using standardized products with sufficient PAC dosage.